Vector-borne diseases in Brazil: climate change and future warming scenarios - Carvalho, Bruno Moreira de; Perez, Leticia Palazzi; Oliveira, Beatriz Fatima Alves de; Jacobson, Ludmilla da Silva Viana; Horta, Marco Aurélio; Sobral, Andrea; Hacon, Sandra de Souza (Sustainability in Debate, 2020)
Climate change affects human health either directly or indirectly, and related impacts are complex, non-linear, and depend on several variables. The various climate change impacts on health include a change in the spatial distribution of vector-borne diseases. In this regard, this study presents and discusses changes in the spatial distribution of climate suitability for visceral leishmaniasis, yellow fever and malaria in Brazil, in different global warming scenarios. Maximum entropy (MaxEnt) was used to construct climate suitability models in warming scenarios. Models were based in climate variables generated by the Eta-HadGEM2 ES regional model, in the baseline period 1965-2005 and RCP8.5 scenario, representing global warming levels of 1,5ºC (2011-2040), 2,0ºC (2041-2070) and 4,0ºC (2071-2099). The three diseases studied are largely influenced by climate and showed different distribution patterns within the country. In global warming scenarios, visceral leishmaniasis found more favorable climate conditions in the Southeastern and Southern regions of Brazil, while climate in the Northern and Center-West regions gradually became more favorable to yellow fever. In malaria scenarios, an increase in favorable climate conditions to its high incidence was observed in the Atlantic Forest, where currently extra-Amazonian cases occur. The scenarios presented herein represent different possible consequences for the health sector in terms of adopting (or not) different measures to mitigate climate change in Brazil, such as reducing the emission of greenhouse gases. Â